1998
DOI: 10.1007/bf02375780
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical promotion of CH4 oxidation on Pd

Abstract: Abstract. The effect of Non-Faradaic Electrochemical Modification of Catalytic Activity (NEMCA effect) or Electrochemical Promotion (EP) was used to promote the methane oxidation reaction to CO2 and H20 over Pd polycrystalline films interfaced with yttria-stabilized zirconia in galvanic cells of the type: CH4, O2, CO 2, Pd/YSZ/Au, CH 4, 02, CO2It was found that by applying positive potentials or currents and thus, supplying O 2-onto the catalyst surface, up to 90-fold increases in CH 4 oxidation catalytic rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
(70 reference statements)
3
15
0
Order By: Relevance
“…Conse- quently, the catalytic reaction rate was increased by anodic polarisation, exhibiting electrophobic behaviour [8]. This result totally agrees with other electrochemical promotion studies on methane combustion, reported by Giannikos et al [17] and Roche et al [34]. These authors also observed electrophobic behaviour under oxidising conditions over palladium catalysts prepared by paste and sputtering, respectively.…”
Section: Original Research Papersupporting
confidence: 89%
See 2 more Smart Citations
“…Conse- quently, the catalytic reaction rate was increased by anodic polarisation, exhibiting electrophobic behaviour [8]. This result totally agrees with other electrochemical promotion studies on methane combustion, reported by Giannikos et al [17] and Roche et al [34]. These authors also observed electrophobic behaviour under oxidising conditions over palladium catalysts prepared by paste and sputtering, respectively.…”
Section: Original Research Papersupporting
confidence: 89%
“…As shown in Figure 8, the rate enhancement ratio was of 5.6. The Faradaic efficiency value was found to be 764 (the highest value reported for the electrochemical promotion of this reaction [17,[33][34][35]). This difference could be explained by the role of ceria film.…”
Section: Original Research Papermentioning
confidence: 98%
See 1 more Smart Citation
“…Owing to the catalytic properties, Pd2 is expected to have the most suitable microstructure. The increase in reaction rate of methane on Pd/YSZ under anodic polarization was already observed by Giannikos et al [17] using Pd paint. They reported typical lambda values of 100 in the temperature range 350-450°C, in good agreement with the results of this study.…”
Section: Resultssupporting
confidence: 51%
“…The reported Faradaic efficiency values were quite low due to the high operating temperatures (650-750°C) and consequent short lifetime of the promoting species and important part of the non catalytic homogeneous reaction. Another study [17] focused on a lower temperature range (350-450°C) and reported higher average lambda values around of 100 and q values up to 90. Frantzis et al [13] found quite similar faradaic efficiency values typically between 30 and 150.…”
Section: Introductionmentioning
confidence: 95%